Providing First Aid to People Experiencing Mental Health Problems: Development of Evidence-Based Guidance Materials for Laypeople - Emmy De Buck (International Journal of First Aid Education)
Background: Family and friends are particularly well placed to recognize early signs of mental health problems, provide initial support, and refer to professional help if needed. This project aimed to develop evidence-based guidance materials for laypeople on how to provide help to people experiencing mental health problems, adapted to the context of Flanders, Belgium. Methods: We performed a systematic literature review for 12 different mental health topics, focusing on communicative support interventions feasible to be performed by laypeople. Systematic literature searches were conducted in MEDLINE, Embase, and PsycNET (October 2018). One reviewer per topic conducted data extraction and methodological quality assessment using the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) methodology. The evidence was used to develop a draft manual, which was presented to a multidisciplinary expert panel involving both content experts (n = 10) and mental health peer workers in training (all people with lived experience) (n = 6). Results: Included studies involved 15 experimental and 75 observational studies, leading to 58 evidence conclusions on communicative interventions, risk factors or protective factors, and their relationship to mental health outcomes. The certainty of the evidence was very low for the majority of the evidence conclusions (84.5%), highlighting the need for expert and stakeholder input to inform practical recommendations. Scientific evidence and expert input were used to formulate 33 individual actions on how to provide first aid to people experiencing mental health problems. The recommendations were made available to laypeople via a guidance manual and a mobile application. Conclusions: Input from the scientific literature and the expert panel were essential to obtain evidence-based guidance materials that were meaningful for practice in a Flemish context.